National Planning Principles and Administration - Planning Commission (Planning Commission, 1948)
K.T. Shah’s National Planning, Principles & Administration provides a comprehensive framework for establishing a planned economy in India, integrating economic growth with social justice. The work emphasizes a balance between centralized planning and local autonomy, advocating for robust administrative machinery, sectoral focus on agriculture, industry, and social services, and equitable resource distribution. It outlines strategies for industrial development, public finance management, labor organization, and cultural integration, while highlighting the need for effective regulatory oversight, particularly in foreign trade. The document proposes the creation of the National Planning Committee to coordinate planning, implement policies, and ensure alignment between central and regional authorities. Overall, it envisions a self-sufficient, egalitarian, and sustainable national economy grounded in social welfare, equitable distribution, and strategic resource management.
National Planning Committee Series
National Planning Committee Series
Keywords: National Planning; Economic Self-Sufficiency; Centralized Planning; Local Autonomy; Industrial Policy; Social Welfare; Administrative Machinery; Public Finance; Trade Regulation; National Planning Committee